Toksidinamik Antibiotika Golongan Aminoglikosida - miladiyah, isnatin (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
The aminoglycosides are the mainstay in the treatment of serious gram-negative systemic mfections. These are the broad spectrum antibiotics, and could be used for many infections of body systems. A disadvantage of theaminoglycosides is their association with nephrotoxicity, ototoxicity, and neurotoxicity, all are associated with elevated serum levels. This article is carried out to give informations about mechanisms of toxicities and their pathology, which is highlighted on aspects of biochemistry, functional, and structural.